Catalytic Desulfurization of Benzothiophene Using Keggin Type Polyoxometalates as catalyst - Aldes Lesbani; Arianti Marpaung; Marieska Verawaty; Hesti Rizki Amalia; Risfidian Mohadi (Chemistry Department, The University of Brawijaya, 2015)
Performance of catalytic desulfurization of benzothiophen (BT) was studied using polyoxometalates as catalyst. Polyoxometalates H3[a-PW12O40] and H4[a-SiW12O40], have different heteroatom in Keggin structure and catalytic activities. Polyoxometalates H3[a-PW12O40] and H4[a-SiW12O40] have high crystallinity with homogeneous distribution particles. Desulfurization of BT using polyoxometalates H3[a-PW12O40] and H4[a-SiW12O40] resulted % conversion up to 99% for 3 h reaction time and at temperature 40 oC. Application of polyoxometalates H3[a-PW12O40] and H4[a-SiW12O40] for crude oil desulfurization showed % conversion of 4-88%. The main functional groups of polyoxometalates still retained after catalytic desulfurization indicated the stability of polyoxometalate compounds